2021
DOI: 10.1044/2020_ajslp-20-00093
|View full text |Cite
|
Sign up to set email alerts
|

Spoken Vocabulary Outcomes of Toddlers With Developmental Delay After Parent-Implemented Augmented Language Intervention

Abstract: Purpose Early intervention using augmentative and alternative communication (AAC) supports both receptive and expressive language skills. However, many parents and clinicians still worry that augmented language intervention might delay or impair speech development. This study aimed to (a) characterize and analyze the speech sound development of toddlers with developmental delay who participated in a parent-implemented language intervention; (b) examine the accuracy of speech sounds among toddlers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Parents are sometimes hesitant to choose an AAC application due to fears that their children will be less motivated to develop spoken language (Donato et al, 2018;Moorcroft et al, 2019). Numerous authors have reported these fears to be unfounded (Donato et al, 2018;Johnston et.al., 2012;Walters et al, 2021). However, it is important to know whether and how prior experience with AAC has an impact on social-communication outcomes for this population to better inform future treatment decisions.…”
Section: Communicative Interventions Targetsmentioning
confidence: 99%
“…Parents are sometimes hesitant to choose an AAC application due to fears that their children will be less motivated to develop spoken language (Donato et al, 2018;Moorcroft et al, 2019). Numerous authors have reported these fears to be unfounded (Donato et al, 2018;Johnston et.al., 2012;Walters et al, 2021). However, it is important to know whether and how prior experience with AAC has an impact on social-communication outcomes for this population to better inform future treatment decisions.…”
Section: Communicative Interventions Targetsmentioning
confidence: 99%
“…AAC is considered a yellow light intervention with a small body of very low-quality evidence supporting its use in children with cerebral palsy to improve their communication, supplement verbal speech and increase peer interactions. However, a more robust evidence exists outside the cerebral palsy population [46], supporting targeting outcomes including (i) development of functional communication skills [47], (ii) improved expressive and receptive language and social skills [48], (iii) verbal speech development [49][50][51], and (iv) quality of life and independence [52].…”
Section: Reading To Advance Cognition and Communicationmentioning
confidence: 99%
“…Parents are sometimes hesitant to choose an AAC application due to fears that their children will be less motivated to develop spoken language (Donato et al, 2018;Moorcroft et al, 2019). Numerous authors have reported these fears to be unfounded (Donato et al, 2018;Johnston et al, 2012;Walters et al, 2021). However, it is important to know whether and how prior experience with AAC has an impact on social-communication outcomes for this population to better inform future treatment decisions.…”
mentioning
confidence: 99%